Human Resource Management Practices and Their Role in Improving the Quality of Healthcare Services Provided in the Palestinian Health Sector - Mohammed Najjar; Ishaq Ibrahim (Journal of Arts, Literature, Humanities and Social Sciences, 2026)
This study aimed to explore the impact of human resource management (HRM) practices on improving the quality of services provided in Palestinian healthcare institutions. The study adopted a descriptive-analytical approach, with the population consisting of all employees in Palestinian healthcare institutions in the West Bank, totaling 9,887 staff members. A stratified random sample of 350 participants was selected from the governorates of Ramallah, Hebron, and Bethlehem. A questionnaire was used to assess HRM practices and service quality, and its validity and reliability were confirmed. The results indicated a high level of HRM practice implementation, with training and development and human resource planning being the most prominent, while incentives and performance evaluation were relatively lower. Service quality was also found to be high, with responsiveness and tangibility dimensions performing best. The study concluded that HRM practices have a statistically significant positive effect on service quality, explaining 74.9% of the variance.